Concept and Design of a 3D Printed Support to Assist Hand Scanning for the Realization of Customized Orthosis. (6th November 2017) - Baronio, Gabriele; Volonghi, Paola; Signoroni, Alberto
Abstract : In the rehabilitation field, the use of additive manufacturing techniques to realize customized orthoses is increasingly widespread. Obtaining a 3D model for the 3D printing phase can be done following different methodologies. We consider the creation of personalized upper limb orthoses, also including fingers, starting from the acquisition of the hand geometry through accurate 3D scanning. However, hand scanning procedure presents differences between healthy subjects and patients affected by pathologies that compromise upper limb functionality. In this work, we present the concept and design of a 3D printed support to assist hand scanning of such patients. The device, realized with FDM additive manufacturing techniques in ABS material, allows palmar acquisitions, and its design and test are motivated by the following needs: (1) immobilizing the hand of patients during the palmar scanning to reduce involuntary movements affecting the scanning quality and (2) keeping hands open and in a correct position, especially to contrast the high degree of hypertonicity of spastic subjects. The resulting device can be used indifferently for the right and the left hand; it is provided in four-dimensional sizes and may be also suitable as a palmar support for the acquisition of the dorsal side of the hand.